Penerapan Model Analisis Risiko Kredit dalam Pengambilan Keputusan Pembiayaan pada UMKM - Rexy Andalangi Maatuil; Trifena Johanis; Kesita Makinggung; Paulina Manoppo (Indo Publishing, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia’s economy; however, access to formal financing remains limited due to high credit risk and inadequate financial record-keeping. This study aims to analyze the application of credit risk assessment models for MSMEs and identify key factors influencing financing eligibility. Using a descriptive–qualitative approach based on secondary data from OJK, Bank Indonesia, BPS, and academic publications, this research examines MSME credit growth, non-performing loan (NPL) trends, external risk factors, and business quality indicators. The findings show that MSME credit growth slowed in 2023–2024, while the NPL ratio remained stable at 3.76%. Rising input prices and weakening consumer purchasing power emerged as the most dominant external factors increasing credit risk. Furthermore, financial bookkeeping significantly influences credit approval, as MSMEs with proper records receive higher approval rates and show lower default risk. These findings highlight the need for more adaptive credit risk models, particularly for micro enterprises, through the integration of alternative digital data.